The ineidence of the eimeria species in partridges ( alectoris graeca) in elazığ vicinity - Nazir DUMANLI; Edip ÖZER (Eurasian Journal of Veterinary Sciences)
The fecal sampls• obtained from partridges which were hunted by the hunters were microscopically examined by means of zinc sulphate flotation method for coccidial agents. Thirtyeight out of sixty partridges (63.33%) were fo und to be infected with Coccidia. Pozitive fecal samples were mixed with a 2.5 percent solution of potassium bichromate and placed separately into petri dishes for spörulation. Two species of Eimeria were found in the examination of sporulated fecal samples. They were Eimeria•caucasica and Eimeria kofoidi. The infestation rateof the Eimeria caucasica, Eimeria kofoidi and mix infection of the se species were 18.33%, 25% and 23.33% respectively.